Academic staff promotion system and its influence on the quality of vocational and technical education - College of Technological Studies, as a case Kuwait - Al-Ali, Salah (Technium Social Sciences Journal, 2021)
The need to enhance local capability is one of most Kuwaiti government priorities that is embodied in the overall governmental plan. In fact, the Kuwaiti government has exerted efforts to forge the College of Technological Studies, CTS, in order to equipped students with the knowledge, skills and attitudes that are required by essential sector in the country’s economy (e.g., Oil and Electricity and Water). However, the success of the College of Technological Studies in achieving its objectives would rely on the competencies of the CTS management and academic staff in meeting industrial requirements. The shaping and enhancing of student’s ability in managing, maintaining, and adapting the imported technology in industries would rely on the level of academic staff knowledge, skills, experience, and attitude in meeting industrial requirements. The efficiency of the promotion system for academic staff would indeed contribute significantly to shaping the standard of the CTS graduates. The need to absorb and evaluate the current status of the CTS academic staff promotion system must be one of highly management priority in order to achieve the CTS overall objectives. The aim of this paper is to identify and examine the efficiency of the academic staff promotion system. Several issues would be investigated and examined. Among which: the criteria’s applied in selected and approving academic journals, the criteria’s required for promoting academic staff, work ethics and its relation to the academic staff promotion system, and the obstacles that might face the CTS management in applying the academic staff promotion system. The paper would conclude that unless the management of the CTS realised and appreciate the significant role of the academic staff promotion system, industries would continue to rely on expatriate for years ahead.